Матричные периодические краевые задачи с сосредоточенным запаздыванием - Чуйко, С.М.; Сысоев, Д.В. (Нелінійні коливання, 2018)
Знайдено необхiднi та достатнi умови iснування розв’язкiв лiнiйної матричної перiодичної задачi
для системи диференцiальних рiвнянь iз зосередженим запiзненням у критичному випадку. Отримано умови iснування та зображення найкращого (у сенсi методу найменших квадратiв) розв’язку
лiнiйної матричної перiодичної задачi для системи диференцiальних рiвнянь iз зосередженим запiзненням. We obtain necessary and sufficient conditions for the existence of solutions of the liner matrix periodic
boundary-value problem for a system of differential equations with concentrated delay in the critical case.
We derive conditions for the existence of the best solution (in the sense of the least-squares method) of the
liner matrix periodic boundary-value problem for the system of differential equations with concentrated
delay and find this solution.